(untitled) (Research, Society and Development, 2022)
The elaboration of this essay, which communicates research results, had the general objective of analyzing, on a theoretical level, relevant aspects of compliance management, namely, its implementation, its objectives, scope and nature; the difference between the Integrity and Compliance Programs; the possible products and the potential resonance in the work environment with regard to risk management. Considering the diversity of normative and institutional sources by compliance area and its natural complexity, the labor specialty was established as a delimitation of approach. This investigation, essentially exploratory and descriptive, resulted in pertinent reflection and considerations about the favorable arguments (reasons, motives and intentions) for the implementation of these Programs, which reinforced the importance of building a culture of integrity, far beyond that of compliance. The idea of integrity goes beyond the normative dimension, reaching the evaluative, philosophical, behavioral and cultural dimension, fundamental to genuine engagement and continuous improvement.